GAMBARAN PENGETAHUAN MASYARAKAT MENGENAI ERUPSI GIGI TETAP MOLAR SATU DAN KARIES GIGI DI DESA WALUYA KECAMATAN CICALENGKA KABUPATEN BANDUNG (Politeknik Kesehatan Kemenkes Bandung, 2020)
Knowledge of dental and oral health is an effort to prevent and overcome dental health problems, one of which is dental caries. The prevalence of caries in the permanent molar one teeth is quite high, 65.77% in the mandibular molar one and 34.74% in the maxillary molar one. One of the reasons is because people's lack understanding about permanent tooth growth. They assume that the permanent teeth of the molar one are deciduous teeth and if there is damage, there will be a replacement. This study aims to determine the description of public knowledge about eruption of permanent molar one and dental caries. This descriptive study was conducted from February to April 2020. The population in this study were residents as many 50 families. The sampling technique was Purposive Sampling and obtained 20 respondents. Data obtained by filling out the questionnaire, processed and presented in the form of a frequency distribution table. The results of the study prove the level of community knowledge regarding eruption of permanent molars, including the good category (5%), quite good category (80%) and bad category (15%). Level of community knowledge regarding dental caries including the good category (55%) and quite good category (45%). And the conclusion that the study prove the level of community knowledge regarding eruption of permanent molars, including the good category (5%), quite good category (80%) and bad category (15%). Level of community knowledge regarding dental caries including the good category (55%) and quite good category (45%). Keywords: Knowledge of oral health, eruption of permanent molar one, dental caries.